An Error Analysis On Writing Descriptive Text Of Student’s Smk Negeri 3 Pematang Siantar - Marhaeni Kartika Dewi Matondang; Anita Purba; Suci Nurmalia (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2023)
The aim of this research is to find out the errors in writing descriptive text of the student’s at SMKN 3 Pematang Siantar. The researcher useddescriptive qualitative method. the population is the students of tenth grade researcher took one classes. From the calculation above, all the number of population is 68 students.So the researcher will take 34 students as a sample. The technique of collecting data was Validityand Reliability.mark omission (OM), addition (AD), misformation (MF) and misordering (MO).The occurance of omission error was 57, the occurance of addition error was 29, the occurrence of misformation error was 5 and the occurances of misordering error was 7. Occurrences which totaled was 79. The most dominant error made by students in writing descriptive text was 57 occurrences or about 72,15 % in omission. Most often errors occurred was error of omission about 29 (36,71%) occurrences. This types of error was usually caused by carelessness. Carelessness occurred when the students are not deliberate to do some mistakes, but the result showed that it was the mistake. The mistake came out from wrong written a phoneme omitted or mistyping